Planning to cope with tropical and subtropical climate change - Tiepolo, Maurizio (De Gruyter, 2021)
This book provides examples of climate change characterization and decision-making tools for subtropical and tropical adaptation planning. It is intended for local operators, physical planners, besides researchers and students of these subjects. The first chapter describes the status of climate planning in large subtropical and tropical cities. The following six chapters discuss hazards (drought, intense precipitations, sea level rise, sea water intrusion) and early warning systems. Nine chapters enlarge on flood risk analysis and preliminary mapping, climate change vulnerability, comparing contingency plans in various scales and presenting experiences centred on adaptation planning. The last three chapters introduce some best practices of weather and climate change monitoring and flood risk mapping and assessment.